Credit ratings and acquisitions - Aktas, Nihat; Petmezas, Dimitris; Servaes, Henri; Karampatsas, Nikolaos (Journal of Corporate Finance, 2021)
There is a curvilinear relation between credit ratings and acquisitions. Non-investment grade firms make more acquisitions as their ratings improve, consistent with the relaxation of financial constraints. However, this pattern reverses for investment grade firms, supporting the view that such firms want to preserve their rating and are concerned about acquisition-related downgrades. Abnormal returns first decrease and then increase as ratings improve. In support of these findings, acquisitions have a negative impact on future ratings only for highly-rated firms. These results indicate that the level of a firm's credit rating has a significant impact on the acquisition process.